Evaluation of solid residues removed from a mangrove swamp in the Sao Vicente Estuary, SP, Brazil - Cordeiro, C. A. M. M. [UNESP]; Costa, T. M. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Mangrove swamps are found in estuaries along the coastal plains of tropical regions and have be subjected to heavy occupation and use pressure due to their privileged locations and abundance of biological resources. The present work evaluated the ecological characteristics and solid wastes accumulated in eight areas along the Santos - Sao Vicente Estuary Complex. The superficially deposited residues at each sampling site were collected and subsequently washed, drained, counted, weighed and separated into classes according to their composition and predominant use. The predominant litter type in terms of density was plastic (62.81%) and, by weight, wood (55.53%). The greatest deposition of residues was associated with areas that were less inclined and that had low plant density levels, indicating that the presence of obstacles was not critical for retaining floating residues in mangrove areas. The presence of the most frequently encountered types of solid waste residues could be explained by local activities. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Mangrove; Estuary; Solid residues; Debris; Marine litter; Baixada Santista